Perancangan Aplikasi Manajemen Keuangan Berbasis Mobile Menggunakan React Native Untuk Meningkatkan Literasi Keuangan Individu - Hielmi Sulaeman; Anita Fira Waluyo (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Financial management is one of the most important problems in human life. By doing financial management, it will be easy to plan their finances. However, this lack of financial literacy is the cause of one of the causes of many people who have not managed their finances well is the lack of time to record their finances. The author proposes to create a mobile-based Financial Management application to improve individual financial literacy. The purpose of making this application is to help individuals manage their finances such as recording income, recording expenses, and applying budgeting methods in doing their financial planning. The research was conducted using the Waterfall research method. This manufacturing process includes system analysis, system design, implementation and testing. The design depicted is in the form of a Data Flow Diagram, Database created, and Wireframe application to be created. Applications that have been created using the React Native framework and use APIs in exchanging data between client and server which then the data will be saved to the database. The app will be tested to see if it's eligible and whether it can help users with financial recordkeeping issues. The results of testing using blackbox testing this application is worth using and works properly. As such, the app has the potential to increase an individual's financial understanding and awareness and encourage the adoption of better financial practices. This technology is proving itself as a valuable tool in personal financial management